Inequality after the 20th century papers from the sixth ECINEQ meeting - Bishop, John A.; RodriU+0301‰guez, Juan Gabriel (Research on economic inequality, 2016)
The essays in this series offer fresh theoretical and methodological insights into the key issues in the field of economic inequality. The content is comprised of highly topical subject matter with key researchers in the field contributing.